1999
DOI: 10.1080/08964289909596742
|View full text |Cite
|
Sign up to set email alerts
|

Semistarvation-Associated Eating Behaviors Among College Binge Eaters: A Preliminary Description and Assessment Scale

Abstract: Binge eating is a consequence of semistarvation in victims of war and famine and in volunteers in rare semistarvation experiments. These behaviors include bizarre mixing of ingredients and adulteration of food; eating inappropriate, soiled, or discarded food; secrecy; deception; and defensiveness. Drastic measures to resist overeating persist long after the semistarvation experience, even when food is plentiful. Binge eating, a central feature of bulimia and sometimes of anorexia nervosa, is prevalent in moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In those cases where patients were monitored after release, nearly all individuals regained most or all of the weight lost during the procedure. Animal models indicate that binge eating persists long after starvation has been reversed (Hagan & Moss, 1997), and studies of human survivors of catastrophic starvation reveal the same pattern (Favaro, Rodella, & Santonastaso, 2000;Hagan et al, 1999). The continuation of binge eating after the alleviation of resource scarcity may re¯ect the workings of an adaptive mechanism designed to gauge the local environmentÐif famine has occurred once during an individual's lifetime, the likelihood may be increased that it will occur again, and hence the persistence of intake-maximizing behaviors may be adaptive.…”
Section: Evidence From Obese Subjectsmentioning
confidence: 90%
See 1 more Smart Citation
“…In those cases where patients were monitored after release, nearly all individuals regained most or all of the weight lost during the procedure. Animal models indicate that binge eating persists long after starvation has been reversed (Hagan & Moss, 1997), and studies of human survivors of catastrophic starvation reveal the same pattern (Favaro, Rodella, & Santonastaso, 2000;Hagan et al, 1999). The continuation of binge eating after the alleviation of resource scarcity may re¯ect the workings of an adaptive mechanism designed to gauge the local environmentÐif famine has occurred once during an individual's lifetime, the likelihood may be increased that it will occur again, and hence the persistence of intake-maximizing behaviors may be adaptive.…”
Section: Evidence From Obese Subjectsmentioning
confidence: 90%
“…Despite strong dedication to the experiment, four subjects engaged in compulsive binge eating. Binge eating is reported in a large number of historical accounts of starvation (Hagan, Whitworth, & Moss, 1999). One Minnesota subject suffered kleptomania; among liberated survivors of the Belsen Nazi concentration camp, impulsive food theft persisted even after it was clear that food was no longer in short supply (Niremberski, 1946).…”
Section: Evidence From Normal Subjectsmentioning
confidence: 98%
“…In a previous study that used the Semistarvation-Associated Behaviors Scale (SSABS), 3 Hagan, Whitworth, and Moss revealed that college students who met the DSM-IV-R criteria for BED engaged in significant numbers of anomalous and bizarre eating behaviors while binge eating. These behaviors included hoarding food, hiding food, secretly eating others' food, eating inappropriate (raw, frozen, soiled, or spoiled) food, and rummaging through garbage for previously discarded food.…”
Section: Index Terms: Dieting Eating Disorders Food Intake Negativmentioning
confidence: 98%
“…This finding paralleled the results found arnong college students classified as "high binge eaters" on the basis of yeslno responses to the proposed BED criteria. 3 We were not surprised because we expected that individuals seeking treatment would have the same or a more intense degree of eating-related pathology as college students who were not in treatment. However, the surprising discovery was that the factors that significantly contributed to chaotic behaviors among the clinical BED population differed from those found to contribute to chaotic eating in the college sample.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation